2016
DOI: 10.1016/j.celrep.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Regulation between SIRT6 and miR-122 Controls Liver Metabolism and Predicts Hepatocarcinoma Prognosis

Abstract: Mice overexpressing the longevity protein SIRT6 or deficient for the liver's most prevalent microRNA miR-122 display a similar set of phenotypes, including improved lipid profile and protection against damage linked to obesity. Here, we show that miR-122 and SIRT6 negatively regulate each other's expression. SIRT6 downregulates miR-122 by deacetylating H3K56 in the promoter region. MiR-122 binds to three sites on the SIRT6 3' UTR and reduces its levels. The interplay between SIRT6 and miR-122 is manifested in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 40 publications
(53 reference statements)
1
69
2
Order By: Relevance
“…Recently, a new study has suggested that many of these functions of SIRT6 may be impacted by a complex interplay with miR-122, the most abundant hepatic microRNA [76]. Like SIRT6 overexpressing mice, miR-122-deficient mice have improved lipid profiles and are resistant to pathologies of diet-induced obesity [66, 77].…”
Section: Regulation Of Glucose and Lipid Homeostasis In Metabolism Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a new study has suggested that many of these functions of SIRT6 may be impacted by a complex interplay with miR-122, the most abundant hepatic microRNA [76]. Like SIRT6 overexpressing mice, miR-122-deficient mice have improved lipid profiles and are resistant to pathologies of diet-induced obesity [66, 77].…”
Section: Regulation Of Glucose and Lipid Homeostasis In Metabolism Anmentioning
confidence: 99%
“…Like SIRT6 overexpressing mice, miR-122-deficient mice have improved lipid profiles and are resistant to pathologies of diet-induced obesity [66, 77]. Elhanati et al now provide evidence that SIRT6 and mi-R122 negatively regulate each other and have opposite effects on fatty acid metabolism and expression of β-oxidation regulatory enzymes [76]. These findings suggest that modulation of miR-122 levels could be useful for treatment of metabolic disorders associated with reduced SIRT6 activity in aging, obesity, or diabetes [45, 69, 78].…”
Section: Regulation Of Glucose and Lipid Homeostasis In Metabolism Anmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, it enhances p53 and E2F-1 chromatin accessibility thus inhibiting apoptosis. Elhanati et al 20 and Lefor et al 21 correlated SIRT6 regulation to two microRNAs (miR-) in two different cancers. At basal conditions, SIRT6 and miR-122 negatively regulate each other in HCC.…”
Section: Sirt6 As a Tumor Promotermentioning
confidence: 99%
“…The miR-122 binds SIRT6 3′ UTR and reduces its levels, while the loss of the negative correlation between SIRT6 and miR-122 expression is significantly associated with better prognosis. 20 In addition, miR-34a plays a key role during The role of SIRT6 is not well known in hematologic malignancies. In multiple myeloma (MM), SIRT6 is highly expressed as adaptive response to genomic stability, and its overexpression is associated to proliferation and poor prognosis.…”
Section: Sirt6 As a Tumor Promotermentioning
confidence: 99%